Placebo effects in hearing-aid trials are reliable. (July 2013) - Dawes, Piers; Hopkins, Rachel; Munro, Kevin J.
Abstract Objective: A recent study suggested that placebo effects are a source of bias in non-blinded hearing-aid trials. Given the potential impact of this finding on the interpretation of non-blinded trials and design of future research trials, the objective of the present study was to investigate the reliability of this effect. Design: Using the same procedure as an earlier study, participants were told that they were taking part in a trial of new hearing-aid technology. Participants compared two devices that were acoustically identical, except one was described as "new" and the other as "conventional". Participants completed a speech-in-noise test, sound quality ratings, and rated overall personal preference for both hearing aids. Study sample: Sixteen adult hearing-aid users. Results: Participants had significantly better mean speech-in-noise performance (70.9% versus 66.8%, Z = 2.30, p = 0.02, effect size Pearson's r = 0.15) and sound quality ratings for the "new" hearing aid (8.1 versus 7.4, Z = − 2.99, p = 0.003, r = 0.28). A significant proportion of participants (75%) expressed an overall preference for the "new" hearing aid (p = 0.001, effect size φc = 0.66). Conclusion: Placebo effects reliably impact on hearing-aid trials. In order to control for placebo effects, double-blind methodology is optimal. However, when double-blinding is not possible other strategies may be appropriate.